Influência das ações educativas nos parâmetros antropométricos e glicêmicos em portadores de diabetes e hipertensão - Favaro, Danielli Teixeira Lima (2015)
Introduction: Diabetes Mellitus and Hypertension are chronic diseases, important and growing public health problem worldwide, considering its epidemic proportions, high financial and social costs for the control and treatment of its complications. Epidemiological data are alarming and are mainly obesity, sedentary lifestyle and aging of the population. The prevention of these diseases and their complications can occur through education in individual health and group. To assist in the control and prevention of diabetes and hypertension, educational programs are an important measure for behavior change, adopting a balanced diet and physical activity. Objective: To analyze the influence of participation in educational groups for the control of diabetes and high blood pressure, anthropometric and clinical parameters. Method: Prospective, descriptive, quantitative, 172 subjects. Sociodemographic, clinical, laboratorial and anthropometric variables in the 1st, 5th and 8th meetings of educational groups were analyzed. Results: 68.6% women; 85.4% white; 64.0% completed elementary education; 47.7% retired; 65.0% diagnosed with diabetes between 6 to 20 years, 90.1% nonsmokers and non-alcoholic. Diastolic blood pressure decreased from 5 to 8ºencontro with (p <0.05). The fasting glucose and glycated hemoglobin decreased from 1st to 5th meeting (p <0.05). They have not changed anthropometric parameters. Conclusion: Given the significance of the results, it is suggested that the strategy of educational groups, following the precepts of longitudinality with qualified and integrated multidisciplinary team, could constitute favorable results for the control of Diabetes and Hypertension.